Connecting research and professionalism in teacher education. Issue 1 (1st January 2021) - Menter, Ian; Flores, Maria Assunção
ABSTRACT: The three main themes of this Special Issue of European Journal of Teacher Education are brought together and considered in the light of what has been said in the articles included. These themes of teacher education, professionalism and research are all dynamic in the way they have been developing over time and also demonstrate considerable geographical diversity in their manifestations. This paper considers the extent to which these temporal and spatial differences indicate a series of tensions, difficulties and paradoxes as the processes of globalisation continue to influence educational policies and practices around the world. The extent to which the outcomes represent increasing convergence or divergence is discussed and the paper concludes by suggesting a number of key questions that may be asked within a particular context in order to make an assessment of the state of health of the teaching profession within that setting.